Does pathological complete response after neoadjuvant chemoradiotherapy associate with long-term survival in esophageal cancer: A systematic review and meta-analysis - Jiajing Sun; Cien Sun; Ying Zhang; Zixian Jin; Thivanka Witharana; Jiawei Li; Chengchu Zhu; Jianfei Shen (BMC Surgery)
Abstract This meta-analysis examines the impact of pathological complete response (pCR) on long-term survival in locally advanced esophageal cancer patients treated with neoadjuvant chemoradiotherapy (NCRT) and surgery. A systematic review of 38 studies found that pCR correlates with improved overall survival (HR = 0.54) and disease-free survival (HR = 0.51). The findings suggest that pCR may serve as a surrogate endpoint for evaluating the survival outcomes of NCRT.